1983
DOI: 10.2172/5472143
|View full text |Cite
|
Sign up to set email alerts
|

Code ALICE B and B: a precompound/evaporation fission code emphasizing neutron yields

Abstract: This report describes a version of the code ALICE/LIVERMORE 82 which has been modified to output neutron yield information of the type one would measure in an experiment gated by measuring a fission fragment. The modified code does the same precompound/compound decay calculations as the code ALICE/LIVERMORE 82, but has additional buffers and algorithms for the neutron yield calculation. We calculate the pre-fission neutron spectra and multiplicities, and post-fission neutron spectra and multiplicities, predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 1 publication
(1 reference statement)
1
32
0
Order By: Relevance
“…It was also shown that, with some freedom in the choice of parameters, these models could give reasonable fit to the observed energy and angular distributions of the emitted particles. The comparisons between experimental results, pre-compound exciton model calculations and intranuclear cascade calculations indicated that the exciton model gave too few pre-compound particles and that these were too soft in spectral distribution for the expected initial exciton configurations [17]. Especially, the intranuclear cascade calculation results indicated that the exciton model deficiency resulted from a failure to properly reproduce enhanced emission from the nuclear surface.…”
Section: Theoretical Cross Section Calculationsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was also shown that, with some freedom in the choice of parameters, these models could give reasonable fit to the observed energy and angular distributions of the emitted particles. The comparisons between experimental results, pre-compound exciton model calculations and intranuclear cascade calculations indicated that the exciton model gave too few pre-compound particles and that these were too soft in spectral distribution for the expected initial exciton configurations [17]. Especially, the intranuclear cascade calculation results indicated that the exciton model deficiency resulted from a failure to properly reproduce enhanced emission from the nuclear surface.…”
Section: Theoretical Cross Section Calculationsmentioning
confidence: 96%
“…Especially, the intranuclear cascade calculation results indicated that the exciton model deficiency resulted from a failure to properly reproduce enhanced emission from the nuclear surface. In order to provide a first order correction for this deficiency, the hybrid model was reformulated by Blann and Vonach [17,25]. In this way, the diffusion surface properties sampled by the higher impact parameters were crudely incorporated into the pre-compound decay formalism, in the geometry dependent hybrid model (GDH).…”
Section: Theoretical Cross Section Calculationsmentioning
confidence: 99%
“…Excitation function of 70 Zn+p, 65 Cu+α, 68 Zn+p and 68 Zn+d reactions were calculated using ALICE-91 and TALYS-1.0 codes [17][18][19]. The codes were used simultaneously to increase the accuracy of calculations.…”
Section: Calculation Of Excitation Functionmentioning
confidence: 99%
“…8, for all four projectile effective energies, in comparison with the values from theoretical evaporation calculations. These evaporation calculations have been carried out with the ALICE code available in Warsaw [37], 16 23 using the standard level density parameter and mass predictions from the Myers-Swiatecki formula. The shape and the positions of maxima are well reproduced by the theory for both two-particle evaporation channels, but the absolute values of crosssections are overestimated.…”
Section: B[e2]t=o384+_ooo4ezbmentioning
confidence: 99%